Polymethylaluminoxane organic frameworks (sMAOF) – highly active supports for slurry phase ethylene polymerisation - Kilpatrick, AFR; Geddes, HS; Turner, ZR; Buffet, J-C; Goodwin, AL; O'Hare, D (Royal Society of Chemistry, 2021)
A series of modified solid polymethylaluminoxane (sMAO) catalyst supports have been developed for slurry phase ethylene polymerisation, using aryl di-ol modifier groups. Characterisation using ICP-MS analysis, X-ray total scattering, SEM–EDX, diffuse FT-IR and solid state NMR spectroscopy shows that the organic linker groups are uniformly distributed in a proposed organic framework stucture we call a “sMAOF”. When used as a support for rac-ethylene{bis(1-indenyl)} zirconium dichloride, (EBI)ZrCl2, these linker modified sMAOF materials provide a 40% enhancement in polymerisation activity with respect to unmodified sMAO: activities of 163 × 103 and 116 × 103 kgPE molZr−1 h−1 at 80 °C for (EBI)ZrCl2 supported on sMAOF(1,4-HO(C6F4)OH) and sMAO, respectively. The observed activity increase is correlated with the higher BET surface area and increased porosity in the linker modified sMAOF activating support.